Review of Disasters, Disaster Response, Risk, and Public Open Spaces in Urban Areas - altim setiawan; Amar; Rivai Mardin (Jurnal Sains dan Teknologi Tadulako, 2026)
The increasing risk of disasters in urban areas demands a new spatial planning paradigm that prioritizes disaster risk reduction (DRR). Public Open Spaces (POPs) not only serve as aesthetic and recreational elements but also have the potential to serve as strategic soft infrastructure in integral disaster management, as demonstrated by current literature and regulations. This study aims to analyze the role of POPs in supporting urban resilience by integrating disaster mitigation concepts into urban spatial planning in Indonesia. The study uses descriptive qualitative literature review with analysis of national regulations (Law No. 24 of 2007, Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency No. 14 of 2022), international frameworks (Sendai Framework, UNDRR), and academic literature related to the disaster management cycle and risk-based urban planning. The results show that POPs have a significant role in four phases of disaster management: (1) mitigation as an ecological buffer zone; (2) preparedness as a training location and assembly point; (3) emergency response as an evacuation space and logistics center; and (4) recovery as a place for socio-psychological rehabilitation. The application of the dual-use planning concept optimizes the RTP function under both normal conditions and in crises. This research contribution strengthens academic understanding of the integral relationship between green infrastructure,spatial planning, and risk reduction and offers policy recommendations for more effective implementation at the local level. The conclusion is that integrating RTP into risk-based spatial planning is a crucial investment for building resilient, sustainable, and disaster-resilient cities in the future.